Synergistic Role of Balanced Scorecard/Activity Based Costing and Goal Programming Combined Model on Strategic Cost Management - Taleghani, Mohammad (International Journal of Economics and Financial Issues, 2017)
During the past few years, we have seen a significant shift in cost accounting and management. In the new business environment, cost management has become a critical skill, but it is not sufficient for simply reducing costs; instead, costs must be managed strategically. Application of a successful Strategic Cost Management (StraCM) system plays the significant role in success of organization performance. In this study, we want to illustrate how the goal programming model in combination with tools of the StraCM can affect in improving organizations’ performance and Optimize cost management decisions making. For this, we present a conceptual model with an integrated approach of Balanced Scorecard (BSC), Activity Based Costing (ABC) and Goal programming model. Then for evaluating the proposed model, a numerical example with its solution procedure will be illustrated. Keywords: Strategic cost management (StraCM); Goal programming; Balanced Scorecard (BSC); Activity Based Costing (ABC) JEL Classifications: L1, M41